Effect of ultrasonic and ozone pre-treatments on pharmaceutical waste activated sludge's solubilisation, reduction, anaerobic biodegradability and acute biological toxicity. (September 2015) - Pei, Jin; Yao, Hong; Wang, Hui; Shan, Dan; Jiang, Yichen; Ma, Lanqianya; Yu, Xiaohua
Highlights: The efficiency of AD on activated sludge in pharmaceutical WWTP has to be improved. Ultrasonic and ozone pre-treatments were tested. Pre-treatments released heavy metals from solid phase into the supernatant. Cu 2+ in the supernatant released by pre-treatments affected the methane production. Acute biological toxicity of sludge was reduced by anaerobic digestion. Abstract: Ultrasonic and ozone pre-treatment technologies were employed in this study to improve the anaerobic digestion efficiency of pharmaceutical waste activated sludge. The sludge solubilisation achieved 30.01% (150, 000 kJ/kg TS) and 28.10% (0.1 g O3 /g TS) after ultrasonic treatment and ozone treatment. The anaerobic biodegradability after ultrasonic treatment was higher compared to ozonation due to the higher cumulative methane volume observed after 6 days (249 ml vs 190 ml). The ozonated sludge released the highest concentration of Cu 2+ into the liquid phase (6.640 mg L −1 ) compared to 0.530 mg/L for untreated sludge and 0.991 mg/L for sonicated sludge. The acute toxicity test measured by luminescent bacteria showed that anaerobic digestion could degrade toxic compounds and result in a reduction in toxicity. The main mechanism of action led to some differences in the treated sludge exhibiting higher potential for methane production from pharmaceutical waste sludge with ultrasonic treatment.